2013
DOI: 10.1021/bi3012093
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Electron Nuclear Double-Resonance Spectroscopy Studies of the Mechanism of Proton-Coupled Electron Transfer at the Tyrosine-D Residue of Photosystem II

Abstract: The solar water-splitting protein complex, photosystem II, catalyzes one of the most energetically demanding reactions in Nature by using light energy to drive the catalytic oxidation of water. Photosystem II contains two symmetrically placed tyrosine residues, YD and YZ, one on each subunit of the heterodimeric core. The YZ residue is kinetically competent and is proposed to be directly involved in the proton-coupled electron transfer reactions of water oxidation. In contrast, the YD proton-coupled electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 70 publications
(145 reference statements)
3
34
0
Order By: Relevance
“…In this case, initial light absorption leads to photoexcitation of the porphyrin, PF 10 , which results in the formation of the photooxidized species, PF 10 ⋅+ , through electron transfer to the solvent matrix ( Charles et al., 2020 ; Gasyna et al., 1984 ; Harbour and Tollin, 1974 ; Linschitz and Rennert, 1952 ; Livingston and Ryan, 1953 ). This is followed by rapid PCET at the BiP moiety, which reduces the PF 10 ⋅+ cation to regenerate the neutral porphyrin with the formation of a phenoxyl radical where the phenolic proton is transferred to the proximal nitrogen atom on the benzimidazole ( Chatterjee et al., 2013 ; Faller et al., 2002 ; Megiatto et al., 2014 ; Zhao et al., 2012 ). The presence of the continuous-wave ( cw ) and magnetic field sweep electron-spin-echo electron paramagnetic resonance (EPR) signal at a g value of 2.004 corresponding to a magnetic field position of 346.1 mT at X-band microwave frequency (9.64 GHz) confirm the formation of the BiP–PF 10 ⋅+ radical (electron spin, S = ½) upon cryogenic illumination ( Figures 3 A and 3B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, initial light absorption leads to photoexcitation of the porphyrin, PF 10 , which results in the formation of the photooxidized species, PF 10 ⋅+ , through electron transfer to the solvent matrix ( Charles et al., 2020 ; Gasyna et al., 1984 ; Harbour and Tollin, 1974 ; Linschitz and Rennert, 1952 ; Livingston and Ryan, 1953 ). This is followed by rapid PCET at the BiP moiety, which reduces the PF 10 ⋅+ cation to regenerate the neutral porphyrin with the formation of a phenoxyl radical where the phenolic proton is transferred to the proximal nitrogen atom on the benzimidazole ( Chatterjee et al., 2013 ; Faller et al., 2002 ; Megiatto et al., 2014 ; Zhao et al., 2012 ). The presence of the continuous-wave ( cw ) and magnetic field sweep electron-spin-echo electron paramagnetic resonance (EPR) signal at a g value of 2.004 corresponding to a magnetic field position of 346.1 mT at X-band microwave frequency (9.64 GHz) confirm the formation of the BiP–PF 10 ⋅+ radical (electron spin, S = ½) upon cryogenic illumination ( Figures 3 A and 3B).…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding g -tensors that are obtained from the DFT calculations of the A , B , and C structures are presented in Table S3 . Previous high-frequency EPR and ENDOR measurements on the redox-active tyrosine-D radical of photosystem II ( Chatterjee et al., 2013 ; Faller et al., 2002 ; Un et al., 1996 , 1994 ) and TiO 2 _ PF 10 BiP triad ( Megiatto et al., 2014 ) have demonstrated that the g X component of the g -tensor for a tyrosyl radical that is oriented along the C-O molecular axis is sensitive to the local environment of the phenolic oxygen atom. In this case, the spin-orbit coupling interaction between the unpaired electron in the singly occupied molecular orbital (SOMO) and the lone pairs of electrons on the phenolic oxygen atom induce a magnetic moment that results in a rather large deviation of the g X component of the g -tensor (e.g., g X of ∼2.008) from the free electron g-value (g e = 2.0023) ( Megiatto et al., 2014 ; Stone, 1963 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we will briefly focus on selected data relating only to the protons/deuterons because they are most relevant to the subject of microsolvation of Y D • . Two types of 2 H ENDOR HFCs have been reported, i.e., where the tyrosyl radical is generated under physiological pH (6.5) 79 and high pH (8.7) 46 conditions. Radicals generated under both conditions give the characteristic g x ≈ 2.0074 signal, 71 which implies that Y D • interacts only with His189; that is, N ε (N τ ) acts as the sole hydrogen bond donor to Y D • .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, high-frequency electronic–nuclear double resonance (ENDOR) spectroscopic experiments indicated a short, strong H-bond between TyrD and His189 prior to charge transfer and elongation of this H-bond after charge transfer (ET and PT). On the basis of numerical simulations of high-frequency 2 H ENDOR data, TyrD-O • is proposed to form a short 1.49 Å H-bond with His189 at a pH of 8.7 and a temperature of 7 K. 27 (Here, the distance is from H to N of His189.) This H-bond is indicative of an unrelaxed radical.…”
Section: Tyrosyl Radical Environmentsmentioning
confidence: 99%